Winter precipitation in Western Italian Alps (1926-2010): trends and connections with the North Atlantic/Arctic Oscillation - TERZAGO, SILVIA; FRATIANNI, SIMONA; Cremonini R. (2013)
Six snow depth and total precipitation time series recorded in Western Italian Alps between 960 and 2177 m a.s.l. have been analyzed to investigate variability and trends over the 1926-2010 period. The results outline a significant decrease of snow depth in the period 1951-2010 ranging from -0.2 cm/y in the lowest station up to -1.4 cm/y in the highest one. The contribution to this negative trend comes mainly from spring. These results have been related to the changes in the amount/frequency of total precipitation and to the temperatures analyzed in former studies. The connections between winter precipitation and large scale atmospheric forcings have been investigated by looking for regular oscillations embedded in the time series. Two different techniques have been used, the MultiTaperMethod and the Monte Carlo Singular Spectral Analysis. Both highlight oscillations corresponding to 2.4-2.7 year periods which are found to be driven by the North Atlantic Oscillation.